The WB Constant Dollar Income Concept: An Interpretation - Syed M. Ahsan; S. Quamrul Ahsan (Center for Economic Studies and ifo Institute (CESifo), 2022)
The present note raises the issue of how best to interpret the World Bank's (WB) much used `constant USD per capita income' concept and similar series. We find that the guide to its construction appearing on the WB data portal to be sketchy. The procedures essentially convert all host-country national accounts data, in USD terms, to a common base year, currently 2015. Laudably, this renders all data internationally comparable, though one may question its cardinality. We show that the concept relies on the market exchange rate of a host-country in the base year, and hence whenever the WB alters its base year as it does every few years, the `constant USD' values are directly affected by the shift in a host country's market exchange rate during the interim period. The latter feature injects an element of randomness in the resulting income concept to the extent the observed exchange rates deviate even temporarily from what one may consider their equilibrium level. Consequently, we recommend replacing the market rate by its `smoothed' version to render the resulting income series more reliable.
Keywords: E31; F31; O11; 330; per capita income; constant USD income; current USD income; GDP deflator